EFFECT OF OCCUPATIONAL HEALTH SAFETY PLANNING IN THE IMPLEMENTATION OF OCCUPATIONAL HEALTH AND SAFETY PROGRAMS IN STATE CORPORATIONS IN NAKURU TOWN, KENYA (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
Occupational health and safety is a fundamental concept that continues to be associated with human resource issues. The importance of OHS programs is founded on the premise that the workforce requires care just like any other resources within an organization. Needless to say, State corporations are subject to health and safety issues. These firms presumptively face numerous challenges bordering on health and safety of their employees. Though, employees are expected to work in environments where their health and safety are assured, sometimes this is not the case. This justifies the essence of having sound OHS programs in place and ensures they are fully implemented. Generally, the study sought to examine the role played by the HR function in the implementation of OHS in the State corporations in Nakuru town, Kenya. In particular, the study investigated the influence of training on OHS programs, appraisal of OHS programs, audit of OHS programs, and planning of OHS programs on the implementation of OHS programs in State corporations. It was guided by four theories which included economic theory, theory of compensating wage differentials, Perrow’s normal accident theory, and social judgment theory. This study adopted descriptive survey research design. The study targeted the 919 employees working with State corporations in Nakuru town. Stratified random sampling technique was used to draw sampled respondents from the target population. A structured questionnaire was employed to collect primary data. Both reliability and validity of the research instrument were determined prior to data collection for the main study. The collected primary data was processed and analyzed with the help of the Statistical Package for Social Sciences (SPSS) analytical tool. Data analysis was in form of both descriptive and inferential statistics. The study findings were presented in form of statistical tables. The study found out that the human resource function played a considerable role in the implementation of OHS programs in State corporations in Nakuru town. More specifically, the implementation of OHS programs in the said organizations was noted to be significantly and positively influenced by training on OHS programs, appraisal of OHS programs, audit of OHS programs, and planning of OHS programs. The study recommended that that training on health and safety issues should be emphasized; appraisal of these programs are upheld and conducted regularly; OHS audit should be regularly conducted by the internal human resource department; and corporations should involve all stakeholders and planning professionals in the planning of OHS matters.